Answer:
6x^2 - x - 15
Explanation:
Hello!
For this equation, we need to multiply the two binomials in the two sets of parentheses. This problem can be solved using FOIL.
Reminder:
FOIL stands for...
First
Outside/Outer
Inside/Inner
Last
We are going to be using this strategy! It shows us what we need to multiply, and in what order:
3x * 2x = 6x^2
3x * 3 = 9x
-5 * 2x = -10x
-5 * 3 = 15
And, all together...
6x^2 + 9x - 10x - 15
Now, we simplify it further... the 9x - 10x = -x
6x^2 - x - 15
Wala!
Hope that helped!
-Mary :)